2021
DOI: 10.3390/cancers13092078
|View full text |Cite
|
Sign up to set email alerts
|

Role of Circulating Tumor DNA in Hematological Malignancy

Abstract: With the recent advances in noninvasive approaches for cancer diagnosis and surveillance, the term “liquid biopsy” has become more familiar to clinicians, including hematologists. Liquid biopsy provides a variety of clinically useful genetic data. In this era of personalized medicine, genetic information is critical to early diagnosis, aiding risk stratification, directing therapeutic options, and monitoring disease relapse. The validity of circulating tumor DNA (ctDNA)-mediated liquid biopsies has received in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 165 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…Detection of MRD in PB mirroring BM and/or EMD would bring obvious advantages to patients and clinicians, allowing frequent and minimally invasive real-time monitoring of the disease [ 83 , 84 , 85 , 86 ]. In fact, the use of a liquid biopsy has been proposed as an alternative approach to monitoring MRD in MM and mainly uses circulating tumor DNA (ctDNA) [ 83 , 87 , 88 ], circulating tumor cells (CTCs) [ 89 , 90 , 91 ], serum monoclonal immunoglobulins [ 14 ], and, recently, EVs [ 44 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detection of MRD in PB mirroring BM and/or EMD would bring obvious advantages to patients and clinicians, allowing frequent and minimally invasive real-time monitoring of the disease [ 83 , 84 , 85 , 86 ]. In fact, the use of a liquid biopsy has been proposed as an alternative approach to monitoring MRD in MM and mainly uses circulating tumor DNA (ctDNA) [ 83 , 87 , 88 ], circulating tumor cells (CTCs) [ 89 , 90 , 91 ], serum monoclonal immunoglobulins [ 14 ], and, recently, EVs [ 44 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diverse biomarkers can be used to track response and risk of relapse. PET imaging and ctDNA analyses have emerged as sensitive means of tracking lymphoma and leukemia regression (48)(49)(50). Q-PCR or deep sequencing methods have provided a picture of CAR-19 expansion and persistence over the first critical weeks and months after treatment (51).…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular testing and biomarkers have been evaluated for detection and diagnosis of hematologic cancers. These include: somatic mutations in preleukaemic hematopoietic stem and progenitor cells (HSPCs), presence of tumor-specific mutations in cell-free DNA (cfDNA) and circulating tumor DNA (ctDNA) [ 7 , 13 , 14 , 15 ]. In our study, an increase in the peripheral blood levels of CD24/CD11b was found among subjects with hematologic malignancies compared to healthy subjects ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%